2013
DOI: 10.1242/bio.20135314
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase modulates human platelet aggregation via actin cytoskeleton reorganization and store-operated calcium entry

Abstract: SummaryMyeloperoxidase (MPO) is a heme-containing enzyme released from activated leukocytes into the extracellular space during inflammation. Its main function is the production of hypohalous acids that are potent oxidants. MPO can also modulate cell signaling and inflammatory responses independently of its enzymatic activity. Because MPO is regarded as an important risk factor for cardiovascular diseases associated with increased platelet activity, we studied the effects of MPO on human platelet functional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…However, the influence of leukocytes on platelet activation and thrombus growth is under-investigated. Here, in line with previous studies (25,(38)(39)(40)(41)(42)(43), granulocytes' activation resulted in granulocyte shape and velocity changes (Fig. 3G-I), as well as in the changes in thrombus area (Fig S4A).…”
Section: Discussionsupporting
confidence: 92%
“…However, the influence of leukocytes on platelet activation and thrombus growth is under-investigated. Here, in line with previous studies (25,(38)(39)(40)(41)(42)(43), granulocytes' activation resulted in granulocyte shape and velocity changes (Fig. 3G-I), as well as in the changes in thrombus area (Fig S4A).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, MPO is known as a heme protein and cellular catalytic enzyme which is released form monocyte and neutrophils. It has been shown that MPO binds to human platelets and triggers platelet activation and aggregation via releasing Ca 2+ from platelets’ intracellular stores [ 62 ]. In addition, ALOX12 is a known arachidonate 12-lipoxygenase and its role in platelets functions is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…MPO is a cationic glycoprotein that can also bind to the surface of neutrophils (123) and platelets (124) via electrostatic carbohydrate-dependent mechanisms, thereby triggering proinflammatory functional activities (125). The priming and activation of neutrophils by inflammatory mediators, such as Toll-like receptor (TLR) ligands (126), GM-CSF (127), TNF-␣, and Ig/Fc receptor-mediated signaling (128), can liberate MPO extracellularly by both degranulation and cell death pathways, including apoptosis and necrosis (108).…”
Section: Granulopoiesismentioning
confidence: 99%